Measuring the experiences of health care for patients with musculoskeletal disorders (MSD): development of the Picker MSD questionnaire. - Jenkinson, C; Coulter, A; Gyll, R; Lindström, P; Avner, L; Höglund, E (2002)
Analysis of data from a survey of patients with musculoskeletal problems (mainly back and neck pain) to develop a core measure of patients' experiences of health care. A secondary purpose was to determine whether a single summary index figure could be generated from the instrument. The data reported here comes from a postal survey of patients attending a spine clinic in Stockholm, Sweden. After attending the clinic patients were mailed a questionnaire. Up to two reminders were sent to nonresponders. Questionnaires were sent to 342 patients. Totally 173 (51%) questionnaires were returned, of which 38.1% respondents were male and 61.2% female. The mean age of patients was 54 years (SD 13.84), ranging from 16 to 88. Sixteen items on the questionnaire were found to constitute a reliable index of patient experience and which seem to be tapping the most important aspects of patient experience. The index score was found to have high construct validity. The instrument provides a core set of issues that should be covered when assessing the quality of care patients attending clinics for musculoskeletal disorders.